Respuesta :

Answer:

D

Step-by-step explanation:

Using the rules of exponents

• [tex]a^{-m}[/tex] ⇔ [tex]\frac{1}{a^{m} }[/tex]

• [tex]a^{\frac{1}{2} }[/tex] ⇔ [tex]\sqrt{a}[/tex]

Hence

[tex]36^{-\frac{1}{2} }[/tex] = [tex]\frac{1}{36^{\frac{1}{2} } }[/tex] = [tex]\frac{1}{\sqrt{36} }[/tex] = [tex]\frac{1}{6}[/tex]

For this case we must find an expression equivalent to:

[tex]36 ^ {- \frac {1} {2}}[/tex]

By definition of power properties we have to:

[tex]a ^ {- 1} = \frac {1} {a ^ 1} = \frac {1} {a}[/tex]

So, rewriting the expression we have:

[tex]\frac {1} {36 ^ {\frac {1} {2}}}=[/tex]

By definition of power properties we have to:

[tex]\sqrt [n] {a ^ m} = a ^ {\frac {m} {n}}[/tex]

So:

[tex]\frac {1} {\sqrt {36}} =\\\frac {1} {\sqrt {6 ^ 2}} =\\\frac {1} {6}[/tex]

Answer:

Option D